Premarital Counseling and its Influence on Church Marriages in Emmanuel Cathedral, Madi and West Nile Diocese - Mary Bacia (Uganda Christian University, 2025)
This pastoral research project examines the impact of premarital counseling on Christian marriages in Emmanuel Cathedral Madi and West Nile Diocese. The study aims to investigate the effectiveness of premarital counseling in promoting healthy and sustainable marriages among Christian couples in the Cathedral. Using a mixed-methods approach, the research explores the perceptions and experiences of married couples, clergy and counselors on the role of premarital counseling in building strong marital relationships. The finding of the study reveal that, premarital counseling suggestively influences the quality of Christian marriages, improving communication, conflict resolution and commitment among couples, defining the roles in premarital counseling. This research also highlights the need for the church to prioritize premarital counseling as an essential factor of its marriage preparation program. The study’s recommendations emphasize the importance of training counselors, developing culturally relevant models and integrating premarital counseling into the Church’s marriage ministry. This research contributes to the development of effective strategies for promoting healthy Christian marriage